2004
DOI: 10.1186/cc2886
|View full text |Cite
|
Sign up to set email alerts
|

Immediate post-operative effects of tracheotomy on respiratory function during mechanical ventilation

Abstract: IntroductionTracheotomy is widely performed in the intensive care unit after long-term oral intubation. The present study investigates the immediate influence of tracheotomy on respiratory mechanics and blood gases during mechanical ventilation.MethodsTracheotomy was performed in 32 orally intubated patients for 10.5 ± 4.66 days (all results are means ± standard deviations). Airway pressure, flow and arterial blood gases were recorded immediately before tracheotomy and half an hour afterwards. Respiratory syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Los cambios en los parámetros ventilatorios y gasométricos no fueron muy grandes como lo han descrito diferentes autores (23)(24)(25)(26), dentro de los cuales la pCO2 se redujo de un promedio de 95,04 antes del procedimiento a 43,7 después del mismo, como la ha descrito Sofi y Wani (22). Sin embargo, es interesante enfatizar que posterior a la traqueotomía el 85 % lograron el destete de la VMA en promedio al día n=5,7, lo que generó un espacio en la terapia para los otros pacientes que lo requerían; en estas circunstancias, valdría la pena señalar dos conceptos: la significancia estadística, donde las pruebas de análisis tienen cierto resultado matemático, y la significancia clínica, que nos parece se refleja muy bien este trabajo, donde los pacientes presentaron cambios muy CARDIO: cardiopatía; DM: diabetes mellitus; F: femenino; HAS: hipertensión arterial sistémica; M: masculino; OBES: obesidad; SAOS: síndrome de la apnea obstructiva del sueño.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los cambios en los parámetros ventilatorios y gasométricos no fueron muy grandes como lo han descrito diferentes autores (23)(24)(25)(26), dentro de los cuales la pCO2 se redujo de un promedio de 95,04 antes del procedimiento a 43,7 después del mismo, como la ha descrito Sofi y Wani (22). Sin embargo, es interesante enfatizar que posterior a la traqueotomía el 85 % lograron el destete de la VMA en promedio al día n=5,7, lo que generó un espacio en la terapia para los otros pacientes que lo requerían; en estas circunstancias, valdría la pena señalar dos conceptos: la significancia estadística, donde las pruebas de análisis tienen cierto resultado matemático, y la significancia clínica, que nos parece se refleja muy bien este trabajo, donde los pacientes presentaron cambios muy CARDIO: cardiopatía; DM: diabetes mellitus; F: femenino; HAS: hipertensión arterial sistémica; M: masculino; OBES: obesidad; SAOS: síndrome de la apnea obstructiva del sueño.…”
Section: Discussionunclassified
“…Por otro lado, Sofi y Wani compararon los cambios en la ventilación en pacientes con IOT y los operados de traqueotomía y encontraron una mejoría en la presión de la vías respiratorias; por lo tanto, una mejoría de la dinámica ventilatoria, lo que confirma la opinión consensuada de que el tubo de traqueotomía en comparación con la IOT disminuye la resistencia respiratoria y se asocia con una mejora de la PaO 2 (22). Otros autores como Amygdalou señalan que los cambios son pequeños y no significativos (23). Diehl (24), Mohr (25) y Davis (26) comentan que hay una mejora mínima en la mecánica pulmonar después de la traqueotomía.…”
Section: Introductionunclassified
“…Most studies about changes in the mechanical properties of the respiratory system after tracheostomy were done $20 years ago and included only surgical procedures, so our population likely better reflects contemporary ICU practice. [18][19][20][21] The clinical indications for tracheostomy include attempts to increase patient comfort and to facilitate weaning. 2 Patient-ventilator asynchronies are associated with increases in the duration of mechanical ventilation, in ICU and hospital length of stays, and in the rate of tracheostomies as well as with anxiety, discomfort, and negative outcomes, so various studies in the past decade aimed to optimize patient-ventilator interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some older studies found improvements in the work of breathing (WOB), pressure-time product (PTP), and auto-PEEP 18,19 ; however, other studies did not confirm these findings. 20 More recent studies measured respiratory mechanics in the operating room for a short period of time immediately after tracheostomy 21 or WOB during spontaneous breathing under different scenarios but not in a beforeand-after protocol. 22 We aimed to assess and compare longitudinal changes in patient-ventilator asynchronies and respiratory system mechanics after tracheostomy in recordings of the 24-h periods before and after the procedure in subjects on mechanical ventilation connected to a system that allows the continuous monitoring of respiratory mechanics and the identification of various asynchronies.…”
Section: Introductionmentioning
confidence: 99%
“…The standard route of access has been with a tracheostomy approach for this subpopulation. However, tracheostomy can cause general, local, early, and late complications including cardiac arrest caused by stimulation of vagus nerve, post hypercapnic shock due to sudden lowering of carbon dioxide level, and aeroembolism 15 . Other complications include hemorrhage, subcutaneous or mediastinal emphysema and recurrent laryngeal or tracheal stricture, hemorrhage from large blood vessels caused by decubitus of vessel walls, trachea-esophageal fistula, extensive granulation, and inflammatory complications 16 .…”
Section: Discussionmentioning
confidence: 99%